2020
DOI: 10.26452/ijrps.v11ispl1.2840
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of COVID-19 on community pharmacy

Abstract: The onset of COVID-19 has harmed community pharmacy. As a result, the current study sought to investigate how the coronavirus disease affected community pharmacies from an economic perspective. Short interviews were conducted with 158 community pharmacies located in Riyadh, Saudi Arabia. The findings showed that most of the community pharmacies incurred losses of over 10% as a result of the COVID-19 pandemic during its first month in Saudi Arabia. Specifically, the findings revealed that 19.6% of the pharmacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…This is in contrast to previous studies on Covid-19 and community pharmacy that have focused on topics such as the use of social distancing and PPE, 22 exposure to Covid-19, 17 the personal resilience of pharmacy teams, 29 or highlighted ways that community pharmacy could support other areas of the health service, 26 with many adopting survey approaches to their studies. 14 , 16 , 17 , 18 , 20 , 22 , 30 Thus, this study, utilising a qualitative, theoretically informed approach, offers a novel perspective on how staff working in community pharmacy adjusted, monitored, and learnt from their performance to continue to deliver safe care during the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to previous studies on Covid-19 and community pharmacy that have focused on topics such as the use of social distancing and PPE, 22 exposure to Covid-19, 17 the personal resilience of pharmacy teams, 29 or highlighted ways that community pharmacy could support other areas of the health service, 26 with many adopting survey approaches to their studies. 14 , 16 , 17 , 18 , 20 , 22 , 30 Thus, this study, utilising a qualitative, theoretically informed approach, offers a novel perspective on how staff working in community pharmacy adjusted, monitored, and learnt from their performance to continue to deliver safe care during the Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…These include the use of Personal Protective Equipment (PPE), 13 , 14 , 15 , 16 , 17 changes to pharmacy layout, 18 , 19 , 20 , 21 , 22 enhanced cleaning and disinfecting of surfaces, 16 , 17 , 18 , 19 , 20 , 21 and the introduction of social distancing measures. 13 , 14 , 16 , 18 , 22 Similarly, evidence of pharmacies reconfiguring their systems and redeploying staff to deliver services such as the expansion of medicines delivery services, 13 , 16 , 23 , 26 or the uptake of technology such as telephone/video consultations and use of social media to engage with customers, have been cited. 24 , 25 , 26 However, the perspectives of staff working in community pharmacy in the UK are largely underrepresented.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies from underlined the direct and indirect consequences of the COVID-19 pandemic on the pharmacy workforce and business. 15,16,[20][21][22][23][24] As the COVID-19 pandemic spreads worldwide, the magnitude and consequences of the economic downturn were significant and still highly uncertain around the world. There have been supply disruptions of pharmaceutical products and products demands caused by lockdowns and transport bans across various countries.…”
Section: Discussionmentioning
confidence: 99%
“…13 The Egyptian government has initiated programs to spread awareness among citizens about the risks of COVID-19 and allow enough medicines and medical supplies ensure to cover local needs Alshammari et al studied the economic impact of COVID-19 on community pharmacy and reported that the Saudi Arabia Ministry of Health should enlighten the public on appropriate health practices and suggested developing financial policies to protect community pharmacies and the private sector from potential losses as well as an expanding role for the community pharmacies to offer home care services. 15 A quantitative surveybased approach from pharmacy professionals across 31/54 Commonwealth countries in Africa, Asia, the Americas, Europe and the Pacific revealed that 90% were being at least somewhat worried and more than 65% were very extremely worried about the impact of COVID-19 on them personally and professionally. 16 Ashiru-Oredope et al have also reported that the majority of the respondents (nearly two-thirds) of 545 respondents found it was somewhat difficult or very difficult to work effectively during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 However, despite the preventive measures, many articles reported the lack of preparation and adaptation of pharmacies due to the scarcity of PPE (Personal Protective Equipment), lack of training for the management of services and knowledge about the virus by a team of professionals for the guidance of the population. 11 , 22 , 23 , 32 , 36 , 48 …”
Section: Main Strategies For Addressing Covid-19mentioning
confidence: 99%